2008
DOI: 10.1039/b714095a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral signatures in angle-resolved valence photoelectron spectroscopy of pure glycidol enantiomers

Abstract: Photoionization of the chiral molecule glycidol has been investigated in the valence region. Photoelectron circular dichroism (PECD) curves have been obtained at various photon energies by using circularly polarized VUV synchrotron radiation and a velocity map imaging technique to record angle-resolved photoelectron spectra (PES). The measured chiral asymmetries vary dramatically with the photon energy as well as with the ionized orbital, improving the effective orbital resolution of the PECD spectrum with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 32 publications
7
82
1
5
Order By: Relevance
“…In the higher resolution PES recorded by Rennie et al 51 with a hemispherical analyzer the electronic band structure is slightly more marked and seen to correlate with the PECD changes. The OVGF calculations published by Rennie et al also correspond to the observed oscillations, which highlights the enhanced sensitivity of PECD to electronic structure when compared to usual observables such as ionization cross--sections -even in the case of congested electronic bands as already observed in camphor 36 and glycidol 13 .…”
Section: Camphor Datasupporting
confidence: 64%
“…In the higher resolution PES recorded by Rennie et al 51 with a hemispherical analyzer the electronic band structure is slightly more marked and seen to correlate with the PECD changes. The OVGF calculations published by Rennie et al also correspond to the observed oscillations, which highlights the enhanced sensitivity of PECD to electronic structure when compared to usual observables such as ionization cross--sections -even in the case of congested electronic bands as already observed in camphor 36 and glycidol 13 .…”
Section: Camphor Datasupporting
confidence: 64%
“…We comment that a general advantage of PECD has been shown in its ability to reveal underlying orbital electronic structure even in spectrally congested regions where individual orbitals are not resolved in the PES. [39,[47][48][49] This arises because there may often be large variations in b 1 (in magnitude and sign) between adjacent orbitals even while the cross sections are quite commensurate -with consequently little distinguishable variation in intensity of the regular spectrum. In a somewhat similar manner, PECD may here provide clues to the position of vibrational transitions, even when these are too weak and the resolution insufficient, to show as significant structure in the PES alone.…”
Section: Trifluoromethyloxiranementioning
confidence: 99%
“…The combination of energy and angular measurement of the photoelectrons provides for PECD phenomena to be resolved into contributions made by individual initial orbitals. 8,9,11 The exceptional size of PECD asymmetry factors, several orders of magnitude greater than typically encountered in normal CD measurements made with isolated molecules (i.e., in the absence of cooperative condensed phase enhancement mechanisms) suggests that high sensitivities are potentially achievable. However, it should be stressed that this arises from the ability of the technique to provide angular resolution of the final state wave function.…”
Section: Introductionmentioning
confidence: 99%
“…The first fully realistic calculations suggested that asymmetry factors of the order of a few 10% should be expected, a prediction which has subsequently been borne out by experiment in a number of different molecules. [2][3][4][5][6][7][8][9][10][11] As a form of photoelectron spectroscopy, PECD is naturally performed under vacuum conditions using vapour phase samples of randomly oriented molecules; either at low pressure ( 5 3 10 25 mbar) in a gas cell or effusive jet, or in a supersonic molecular beam in the spectrometer interaction region. In either case the sample molecules are effectively isolated, noninteracting and nonsolvated.…”
Section: Introductionmentioning
confidence: 99%